A kind of erosion-resistant lightweight fire-resistant spray coating and preparation method thereof

Through the process of step-by-step addition and rapid stirring, the raw material components and binding performance of refractory spray coatings are adjusted, and the problem that existing refractory spray coatings are difficult to meet multiple performance requirements at the same time in high-temperature kiln environments are solved, and refractory spray coatings with low rebound rate, fast sintering, good binding performance and corrosion resistance are prepared.

CN116573945BActive Publication Date: 2025-04-25WUHAN METALLURGY ARCHITECTURE RES YUAN CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310622532.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2025-04-25
Estimated Expiration
2043-05-30

AI Technical Summary

Technical Problem

The existing refractory spray coatings are difficult to meet the requirements of low rebound rate, fast sintering, good bonding performance, peel resistance and corrosion resistance in high-temperature kiln environments, especially in alkaline working environments.

Method used

By adding materials such as calcium hexaluminate particles, magnesium aluminum spinel fine powder, alumina fibers, calcium lignin sulfonate and calcium aluminate cement in steps and stirring quickly to form premixes and mixtures, and then adding additives such as borax and sodium oxalate to adjust the hardening and bonding properties of raw material components and improve the anti-erosion and sintering properties of spray coatings.

Benefits of technology

The prepared corrosion-resistant lightweight refractory spray coating has the characteristics of low rebound rate, fast sintering, high early strength, good binding performance, low thermal conductivity and corrosion resistance. It is suitable for lining materials for high-temperature industrial kilns, especially in alkaline environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of refractory materials, and discloses a corrosion-resistant lightweight refractory spray coating and a preparation method thereof. The preparation method comprises the following steps: step 1, mixing calcium hexaaluminate particles, magnesium aluminum spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement to obtain a premix; step 2, adding borax to the premix and stirring to obtain a mixture; step 3, adding water to the mixture and stirring to obtain a precursor material; step 4, adding sodium oxalate to the precursor material and stirring, and then adding water and stirring to obtain a corrosion-resistant lightweight refractory spray coating. The preparation process of the present invention is simple, and the prepared spray coating is easy to construct, fast sintering, high early strength, good bonding performance, and has the characteristics of low thermal conductivity and corrosion resistance, and is widely applicable to lining materials of high-temperature industrial kilns in alkaline working environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a corrosion-resistant lightweight refractory spray coating and a preparation method thereof. Background Art

[0002] Refractory spray coating is an important component of amorphous refractory materials. According to different bonding systems, it can be divided into dry spray coating and wet spray coating. It is widely used in the construction and repair of high-temperature industrial kiln linings. Unlike shaped products or prefabricated parts, refractory spray coating has no preforming process and mainly relies on the material's own bonding system to form "adhesion". It can only produce sintering strength under the high temperature conditions of kiln service. Therefore, refractory spray coating needs to meet the following requirements:

[0003] (1) Low rebound rate. The spray coating is attached to the inner lining of the high-temperature kiln through the spraying equipment, but some of it will still rebound and fall off. Reducing the rebound rate of refractory spray coating has always been the focus of research work.

[0004] (2) Good sintering performance. Whether the spray coating is used as a lining or a repair material, it needs to be able to sinter quickly and form good sintering fusion and integrity with the substrate.

[0005] (3) Strong bonding performance. The selection of refractory spray coating binder needs to be determined according to the main material. Good bonding performance is an important guarantee for the early strength of the spray coating.

[0006] (4) Excellent anti-stripping property. During the service of the spray coating in a high-temperature kiln, the escape of the binder easily produces pores or cracks, which causes structural peeling.

[0007] (5) Good thermal insulation and corrosion resistance. Spray coatings should be made of light materials with low specific gravity. They can not only have good thermal insulation effects, but also reduce the weight of the material and prevent early rebound and shedding. However, there is a certain contradiction between thermal insulation and corrosion resistance. Although maintaining a certain porosity of the spray coating is beneficial to thermal insulation, it damages its corrosion resistance.

[0008] Patent CN115124367A discloses an acid- and alkali-resistant spray coating for cement kilns and a preparation method thereof. By adding ultrafine powder and pore-forming agent, the spray coating has the advantages of high density and relatively high porosity, ensuring its acid- and alkali-resistant corrosion resistance, and the weight is not too large, which does not affect the normal use of the cement kiln. However, the opening will have a significant negative impact on the anti-stripping property of the spray coating. Patent CN101492305A discloses a mullite refractory spray coating, which uses mullite, pure calcium aluminate cement and silica fume as raw materials, and forms interconnected pores by adding explosion-proof agents to achieve the purpose of quick-drying explosion-proof. However, the formation of interconnected pores will greatly reduce the corrosion resistance of the spray coating. It can be seen that it is very difficult to meet the above requirements at the same time. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a corrosion-resistant lightweight refractory spray coating and a preparation method thereof in view of the shortcomings of the prior art. The preparation process is simple, the prepared spray coating is easy to construct, sintered quickly, has high early strength, good bonding performance, and has the characteristics of low thermal conductivity and corrosion resistance. It is widely suitable for lining materials of high-temperature industrial kilns in alkaline working environments.

[0010] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing a corrosion-resistant lightweight refractory spray coating, comprising the following steps:

[0011] Step 1, mixing calcium hexaaluminate particles, magnesium aluminum spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement to obtain a premix;

[0012] Step 2, adding borax to the premix and stirring to obtain a mixture;

[0013] Step 3, adding water to the mixture and stirring to obtain a precursor material;

[0014] Step 4, adding sodium oxalate to the precursor material and stirring, and then adding water and stirring to obtain a corrosion-resistant and lightweight fire-resistant spray coating.

[0015] In the above scheme, the mass ratio of the calcium hexaaluminate particles, magnesium aluminate spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement is 100:(25-30):(12-18):(0.5-1.5):(6-10).

[0016] In the above scheme, the added amount of borax is 2.5-4.5% of the mass of the premix.

[0017] In the above scheme, the amount of sodium oxalate added is 0.5-1.5% of the mass of the precursor material.

[0018] In the above scheme, the amount of water added in step 3 is 2-3% of the mass of the mixed material; the amount of water added in step 4 is 2-4% of the mass of the precursor material.

[0019] In the above scheme, the stirring rate in steps 1 to 4 is 40 to 50 r / min.

[0020] In the above scheme, the stirring time of step 1 is 15 to 20 minutes, the stirring time of step 2 is 5 to 6 minutes, and the stirring time of step 3 is 3 to 5 minutes; the stirring time after adding sodium oxalate in step 4 is 3 to 5 minutes, and the stirring time after adding water is 2 to 3 minutes.

[0021] In the above scheme, the particle size distribution of the calcium hexaaluminate particles is that the mass ratio of particles with a particle size of 0.1-0.3 mm, a particle size of 0.8-1 mm, and a particle size of 1.3-1.5 mm is 100:(15-30):(10-15); the CaO content of the calcium hexaaluminate particles is 8-10%, and the sphericity is 0.8-0.85.

[0022] In the above scheme, the particle size of the magnesium aluminum spinel fine powder is 70-80 μm, and the Al2O3 content is 70-75%.

[0023] In the above scheme, the Al2O3 content of the alumina fiber is 80-90%, the length is 1-4 mm, and the diameter is 15-20 μm.

[0024] In the above scheme, the calcium lignin sulfonate, calcium aluminate cement, borax and sodium oxalate are all industrially pure.

[0025] The invention also provides a corrosion-resistant and lightweight fire-resistant spray coating, which is prepared by the method.

[0026] In the above scheme, the rebound rate of the erosion-resistant lightweight fire-resistant spray coating is 2-3%, and the volume density after drying at 110°C × 12h is 2.38-2.65g / cm 3 After drying at 110℃×12h, the room temperature compressive strength is 40~45MPa, the thermal conductivity after firing at 1400℃×3h is 1.6~1.8W / (m·K), the high temperature flexural strength at 1400℃×1h is 8.5~12.8MPa, and the erosion index of the static crucible method slag resistance test at 1100℃×3h is 1.8~2.5%.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The present invention adopts the method of "stepwise addition", that is, the lean material is fully premixed first, and then a binder is added and combined with a rapid stirring process. On the one hand, the hardening of the raw material components is adjusted to enhance the full contact of the raw materials of each component, and on the other hand, the water seepage of the spray coating is reduced and the plasticity and bonding force of the spray coating are improved.

[0029] (2) The present invention uses spherical calcium hexaaluminate particles as aggregate, and forms an aggregate space structure through graded discontinuous distribution, thereby achieving lightweight spray coating. In addition, calcium hexaaluminate has a low thermal conductivity, and both magnesium aluminum spinel and calcium hexaaluminate have good chemical corrosion resistance, which effectively improves the corrosion resistance of the spray coating.

[0030] (3) The present invention uses the hydration of calcium aluminate cement to produce good early strength, and uses alumina fiber as a "bridge" to be embedded in the "fragment" structure of the hydration product of calcium aluminate cement to play a connecting role. At the same time, it is beneficial to the discharge of gases such as water, reduces the rebound rate of the spray coating, and improves the construction performance of the spray coating.

[0031] (4) The present invention utilizes borax hydrolysis to form B(OH) 4– The long chains of the groups produce chemical bonds, which improve the bonding performance of the spray coating; and under high-temperature service conditions, a liquid phase is produced, and through the in-situ formation of ceramic phases such as aluminum borate, the rapid sintering and fusion of the material is promoted, effectively improving the high-temperature anti-flaking performance of the spray coating.

[0032] (5) The present invention utilizes the introduction of sodium oxalate to adjust the hardening rate of cement and prolong the construction time of the spray coating; in addition, the dissolution reaction of sodium oxalate with alumina fiber at high temperature promotes the connection of calcium hexaaluminate spherical materials, improves the sintering bond strength of aggregate-matrix, and further improves the corrosion resistance of the spray material.

[0033] Therefore, the present invention has the characteristics of simple preparation process. The prepared corrosion-resistant lightweight refractory spray coating is easy to construct, sintered quickly, has high early strength, good bonding performance, and has the characteristics of low thermal conductivity and corrosion resistance. It is widely suitable for lining materials of high-temperature industrial kilns in alkaline working environments. DETAILED DESCRIPTION

[0034] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0035] In the following embodiments, the CaO content of the calcium hexaaluminate particles used is 8-10%, and the sphericity is 0.8-0.85; the particle size of the magnesium aluminum spinel fine powder used is 70-80 μm, and the Al2O3 content is 70-75%; the Al2O3 content of the alumina fiber used is 80-90%, the length is 1-4 mm, and the diameter is 15-20 μm; the calcium lignin sulfonate, calcium aluminate cement, borax, and sodium oxalate used are all industrially pure.

[0036] In the following examples, the rebound rate was determined by the method of GB / T 41503-2022, the bulk density was determined by the method of YB / T5200-1993, the compressive strength was determined by the method of GB / T 5072-2008, the thermal conductivity was determined by the method of GB / T 4130-2005, the high-temperature flexural strength was determined by the method of GB / T 3002-2017, and the static crucible method slag resistance test was carried out by the method of GB / T 8931-2007 to determine the erosion area percentage as the erosion index.

[0037] Example 1

[0038] A method for preparing a corrosion-resistant lightweight fire-resistant spray coating comprises the following steps:

[0039] Step 1, mixing calcium hexaaluminate particles, magnesium aluminum spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement in a mass ratio of 100:27:15:0.8:6, stirring for 15 minutes to obtain a premix;

[0040] Step 2, adding 2.8% borax by weight of the premix to the premix, stirring for 5 minutes to obtain a mixture;

[0041] Step 3, adding 2% water by weight of the mixture to the mixture, stirring for 5 minutes to obtain a precursor material;

[0042] Step 4, adding 0.8% sodium oxalate by weight of the precursor material to the precursor material, stirring for 3 minutes, and then adding 3% water by weight of the precursor material, stirring for 2 minutes to obtain a corrosion-resistant and lightweight fire-resistant spray coating.

[0043] In the above preparation steps, the particle size distribution of the calcium hexaaluminate particles used is that the mass ratio of particles with a particle size of 0.1-0.3 mm, a particle size of 0.8-1 mm, and a particle size of 1.3-1.5 mm is 100:25:12; the stirring rate in steps 1 to 4 is 45 r / min.

[0044] The corrosion-resistant lightweight refractory spray coating prepared in this embodiment was tested: the rebound rate was 2%; the volume density after drying at 110°C × 12h was 2.47g / cm 3 ; The room temperature compressive strength after drying at 110℃×12h is 43MPa; the thermal conductivity after firing at 1400℃×3h is 1.6W / (m·K); the high temperature flexural strength at 1400℃×1h is 9.7MPa; the erosion index of the static crucible method slag resistance test at 1100℃×3h is 2.2%.

[0045] Example 2

[0046] A method for preparing a corrosion-resistant lightweight fire-resistant spray coating comprises the following steps:

[0047] Step 1, mixing calcium hexaaluminate particles, magnesium aluminum spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement in a mass ratio of 100:30:12:1.2:8, stirring for 16 minutes, and obtaining a premix;

[0048] Step 2, adding 3.2% borax by weight of the premix to the premix, stirring for 6 minutes to obtain a mixture;

[0049] Step 3, adding 2.5% water by weight of the mixture to the mixture, stirring for 3 minutes to obtain a precursor material;

[0050] Step 4, adding 1.2% sodium oxalate by weight of the precursor material to the precursor material, stirring for 4 minutes, and then adding 4% water by weight of the precursor material, stirring for 3 minutes to obtain a corrosion-resistant and lightweight fire-resistant spray coating.

[0051] In the above preparation steps, the particle size distribution of the calcium hexaaluminate particles used is that the mass ratio of particles with a particle size of 0.1-0.3 mm, a particle size of 0.8-1 mm, and a particle size of 1.3-1.5 mm is 100:18:15; the stirring rate in steps 1 to 4 is 48 r / min.

[0052] The erosion-resistant lightweight refractory spray coating prepared in this embodiment was tested: the rebound rate was 3%; the volume density after drying at 110°C × 12h was 2.55g / cm 3 ; The room temperature compressive strength after drying at 110℃×12h is 42MPa; the thermal conductivity after firing at 1400℃×3h is 1.8W / (m·K); the high temperature flexural strength at 1400℃×1h is 11.5MPa; the erosion index of the static crucible method slag resistance test at 1100℃×3h is 1.8%.

[0053] Example 3

[0054] A method for preparing a corrosion-resistant lightweight fire-resistant spray coating comprises the following steps:

[0055] Step 1, mixing calcium hexaaluminate particles, magnesium aluminum spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement in a mass ratio of 100:26:16:0.6:9, stirring for 18 minutes, and obtaining a premix;

[0056] Step 2, adding 4% borax by weight of the premix to the premix, stirring for 5 minutes to obtain a mixture;

[0057] Step 3, adding 3% water by weight of the mixture to the mixture, stirring for 4 minutes to obtain a precursor material;

[0058] Step 4, adding 0.6% of sodium oxalate by weight of the precursor to the precursor, stirring for 3 minutes, and then adding 3% of water by weight of the precursor, stirring for 2 minutes to obtain a corrosion-resistant and lightweight fire-resistant spray coating.

[0059] In the above preparation steps, the particle size distribution of the calcium hexaaluminate particles used is that the mass ratio of particles with a particle size of 0.1-0.3 mm, a particle size of 0.8-1 mm, and a particle size of 1.3-1.5 mm is 100:20:10; the stirring rate in steps 1 to 4 is 50 r / min.

[0060] The erosion-resistant lightweight fire-resistant spray coating prepared in this embodiment was tested: the rebound rate was 3%; the volume density after drying at 110°C × 12h was 2.52g / cm3 ; The room temperature compressive strength after drying at 110℃×12h is 40MPa; the thermal conductivity after firing at 1400℃×3h is 1.6W / (m·K); the high temperature flexural strength at 1400℃×1h is 8.5MPa; the erosion index of the static crucible method slag resistance test at 1100℃×3h is 2.3%.

[0061] Comparative Example 1

[0062] A method for preparing a spray coating comprises the following steps:

[0063] Step 1, mixing calcium hexaaluminate particles, magnesium aluminum spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement in a mass ratio of 100:40:10:2:4, stirring for 15 minutes to obtain a premix;

[0064] Step 2, adding 2% borax by weight of the premix to the premix, stirring for 5 minutes to obtain a mixture;

[0065] Step 3, adding 1% water by weight of the mixture to the mixture, stirring for 5 minutes to obtain a precursor material;

[0066] Step 4, adding 2% sodium oxalate by weight of the precursor material to the precursor material, stirring for 3 minutes, and then adding 5% water by weight of the precursor material, stirring for 5 minutes to obtain a spray coating.

[0067] In the above preparation steps, the particle size distribution of the calcium hexaaluminate particles used is that the mass ratio of particles with a particle size of 0.1-0.5 mm, a particle size of 0.5-1 mm (excluding 0.5 mm), and a particle size of 1-1.5 mm (excluding 1 mm) is 100:30:30; the stirring rate in steps 1 to 4 is 25 r / min.

[0068] The spray coating prepared in this comparative example was tested: the rebound rate was 5%; the volume density after drying at 110°C × 12h was 2.24g / cm 3 ; The room temperature compressive strength after drying at 110℃×12h is 35MPa; the thermal conductivity after firing at 1400℃×3h is 1.5W / (m·K); the high temperature flexural strength at 1400℃×1h is 6.6MPa; the erosion index of the static crucible method slag resistance test at 1100℃×3h is 4.7%.

[0069] It can be seen from the test data of Example 1 and Comparative Example 1 that the raw material components have a significant impact on the performance of the spray coating. Under similar preparation processes, the adjustment of the raw material component content, the change of the raw material particle size distribution, and the reduction of the stirring rate cause the reduction of the bonding and sintering performance of the spray coating, and damage the high-temperature mechanical properties of the spray coating (reduced high-temperature flexural strength), and weaken the anti-slag performance of the spray coating (increased erosion index).

[0070] Comparative Example 2

[0071] A method for preparing a spray coating comprises the following steps:

[0072] Step 1, mixing calcium hexaaluminate particles, magnesium aluminum spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement in a mass ratio of 100:27:15:0.8:6, stirring for 15 minutes to obtain a premix;

[0073] Step 2, adding 2.8% of borax, 0.8% of sodium oxalate and 5% of water by weight of the premix to the premix, stirring for 15 minutes to obtain a spray coating.

[0074] In the above preparation steps, the particle size distribution of the calcium hexaaluminate particles used is that the mass ratio of particles with a particle size of 0.1-0.3 mm, a particle size of 0.8-1 mm, and a particle size of 1.3-1.5 mm is 100:25:12; the stirring rate in steps 1 to 2 is 40 r / min.

[0075] The spray coating prepared in this comparative example was tested: the rebound rate was 6%; the volume density after drying at 110°C × 12h was 2.22g / cm 3 ; The room temperature compressive strength after drying at 110℃×12h is 25MPa; the thermal conductivity after firing at 1400℃×3h is 2.1W / (m·K); the high temperature flexural strength at 1400℃×1h is 5.8MPa; the erosion index of the static crucible method slag resistance test at 1100℃×3h is 6.4%.

[0076] It can be seen from the test data of Example 1 and Comparative Example 2 that the preparation process is an important factor affecting the performance of the spray coating. When the raw material components are similar, the room temperature and high temperature mechanical properties of the prepared spray coating are reduced by the method of one-time feeding and overall mixing, and the slag resistance performance is deteriorated. This is because the step-by-step feeding, stirring and mixing can utilize the staged reaction of the additives to form a combination, which is conducive to adjusting the plasticity of the spray coating, thereby achieving full contact of the raw material components and improving the thermodynamic properties of the spray coating.

[0077] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A method for preparing a corrosion-resistant lightweight refractory spray coating, characterized in that: The following steps are involved: Step 1, mixing calcium hexaaluminate particles, magnesium aluminum spinel fine powder, alumina fiber, calcium lignin sulfonate and calcium aluminate cement in a mass ratio of 100: (25-30): (12-18): (0.5-1.5): (6-10) to obtain a premix; wherein the particle size distribution of the calcium hexaaluminate particles is that the mass ratio of particles with a particle size of 0.1-0.3 mm, a particle size of 0.8-1 mm, and a particle size of 1.3-1.5 mm is 100: (15-30): (10-15); Step 2, adding 2.5-4.5% of the mass of the premix of borax to the premix and stirring to obtain a mixture; Step 3, adding water to the mixture and stirring to obtain a precursor material; Step 4, adding 0.5-1.5% of sodium oxalate by mass of the precursor into the precursor material and stirring, and then adding water and stirring to obtain a corrosion-resistant and lightweight fire-resistant spray coating; wherein the stirring rate in steps 1 to 4 is 40-50 r / min.

2. The method for preparing the erosion-resistant lightweight refractory spray coating according to claim 1, characterized in that: The amount of water added in step 3 is 2-3% of the mass of the mixture; the amount of water added in step 4 is 2-4% of the mass of the precursor material.

3. The method for preparing the erosion-resistant lightweight refractory spray coating according to claim 1, characterized in that: The stirring time of step 1 is 15-20 min, the stirring time of step 2 is 5-6 min, and the stirring time of step 3 is 3-5 min; the stirring time after adding sodium oxalate in step 4 is 3-5 min, and the stirring time after adding water is 2-3 min.

4. The method for preparing the erosion-resistant lightweight refractory spray coating according to claim 1, characterized in that: The calcium hexaaluminate particles have a CaO content of 8-10% and a sphericity of 0.8-0.

85.

5. The method for preparing the erosion-resistant lightweight refractory spray coating according to claim 1, characterized in that: The particle size of the magnesium aluminum spinel fine powder is 70-80 μm, and the Al2O3 content is 70-75%.

6. The method for preparing the erosion-resistant lightweight refractory spray coating according to claim 1, characterized in that: The Al2O3 content of the alumina fiber is 80-90%, the length is 1-4 mm, and the diameter is 15-20 μm.

7. A corrosion-resistant and lightweight fire-resistant spray coating prepared by the preparation method according to any one of claims 1 to 6.

8. The erosion-resistant lightweight refractory spray coating according to claim 7, characterized in that: The erosion-resistant lightweight refractory spray coating has a rebound rate of 2-3% and a bulk density of 2.38-2.65 g / cm after drying at 110°C for 12 hours. 3 The room temperature compressive strength after drying at 110℃×12h is 40~45 MPa, the thermal conductivity after sintering at 1400℃×3h is 1.6~1.8 W / (m·K), the high temperature flexural strength at 1400℃×1h is 8.5~12.8 MPa, and the erosion index of the static crucible method slag resistance test at 1100℃×3h is 1.8~2.5%.

Citation Information

Patent Citations

  • Mullite flame-proof spray paint

    CN101492305A

  • Acid and alkali corrosion resistant spray coating for cement kiln and preparation method of acid and alkali corrosion resistant spray coating

    CN115124367A

  • Calcium hexaluminate and corundum composite porous light heat insulation refractory material and preparation method thereof

    CN101928153A

  • Anhydrous stemming and preparation method thereof

    CN102951909A